Fuel gas production from peanut shell waste using a modular downdraft gasifier with the thermal integrated unit. (July 2015) - Nisamaneenate, Jurarat; Atong, Duangduen; Sornkade, Panchaluck; Sricharoenchaikul, Viboon
Abstract: Downdraft gasifier is a preferable method for carrying out biomass gasification because the produced gas has viable heating value with low tar content and can be cleaned to high purity, suitable for IC engine usage and chemical processing applications. This is due to throat section design in the downdraft gasifier which helps reducing the tar content through intense heat. In this study, a modular concept is applied to bring the gasification process to the place where feedstock is abundant which may yield better economic returns through additional utilization of various wastes and reduced transportation cost. The main objective is to study the potential of peanut shell waste conversion using a modular fixed bed gasifier coupled with thermal integration unit. The thermal integration unit was applied to return hot fuel gas exiting the gasifier to drying and pyrolysis zones of the reactor. The effects of gasification on gas flow rate of approximately 1.62–3.54 m 3 /hr and the performance of the gasification process were characterized in term of gas composition, conversion, gasification efficiency, biomass consumption rate, and specific gasification rate. The thermal integration unit also improved gasification reaction in which lower tar content and high gas production efficiency can be achieved. The results suggested that the air flow rate had integrated effects on product yield and composition; optimum of air flow rate resulted in the conversion of carbon converted to CO, CO2, and CH4 of 47.21%, 37.88%, and 8.76% respectively whereas hydrogen converted to H2 and CH4 were 49.31% and 20.91%, respectively at 3.06 m 3 /hr air. This was due to the chemical decomposition in the presence of oxygen and heat from combustion which supported the gasification reactions. The quality of product gas is found to be dependent on the air flow rate and continuity of feeding material. The produced gas from gasification of peanut shell waste contained quality combustible gases, which can be readily used in heat and power applications. Highlights: One of the first researches on peanut shell gasification. Improved gasification reaction with low tar content using thermal integration unit. Absence of blockage and fouling from tar formation. Modular gasification system to fuel gas engine in remote communities.